Congenital acute megakaryocytic leukemia - N B Mathur; Neha Joshi; T Singh; Meeta Singh (Indian Journal of Medical and Paediatric Oncology)
Congenital leukemia (CL) is an extremely rare disorder in the newborn, significant proportion of which is of myeloid origin, primarily of M4 or M5 morphology. As compared to pediatric leukemia, CL is a more aggressive disease. Acute myeloid leukemia (AML-M7) or acute megakaryocytic leukemia is a rare type of AML with an incidence of 0.5 per million per year. Median age of presentation is 6 years, and children may present with a broad variety of symptoms including low-grade fever, diarrhea, easy bruising, failure to gain weight and life-threatening conditions.